2016
DOI: 10.4274/tjh.2016.0031
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Angiogenesis in Haemophilic Arthropathy: Where Do We Stand and Where Are We Going?

Abstract: Haemophilia is an inherited bleeding disorder that can lead to degenerative joint arthropathy due to recurrent bleeding episodes affecting the musculoskeletal system of the patient. The cause of bleeding can be either traumatic or spontaneous. The pathogenesis of haemophilic arthropathy is unclear as many factors like iron, inflammatory cytokines, and angiogenic factors contribute to this process. Blood into joints can deteriorate the bone to such an extent that the patient experiences pain, reduction of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Angiogenesis is known to occur mainly in the bone marrow and vascular stem cells. Studies have reported that angiogenic factors such as VEGF, ANG‐1, ANG‐2, and fibroblast growth factor participate in endothelial cell proliferation 13 . It was previously reported that serum concentrations of VEGF, VEGFR, ANG‐1, and Fms‐like tyrosine kinase‐1 are associated with inflammatory markers and bone resorption in patients with haemophilia 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis is known to occur mainly in the bone marrow and vascular stem cells. Studies have reported that angiogenic factors such as VEGF, ANG‐1, ANG‐2, and fibroblast growth factor participate in endothelial cell proliferation 13 . It was previously reported that serum concentrations of VEGF, VEGFR, ANG‐1, and Fms‐like tyrosine kinase‐1 are associated with inflammatory markers and bone resorption in patients with haemophilia 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increase in angiogenic factor levels was corroborated by a corresponding increase in mRNA expression of ENG, HIF-1A, PGE-2, and VEGFA.Studies on animal models and cell cultures have established the role of ENG in vascular development and tumour angiogenesis. Since high-degree of neo-angiogenesis and aberrant vascular remodelling are thought to underlie the pathogenesis in haemophilic arthropathy,13 we set out to investigate the mRNA expression and protein levels of ENG in haemophilia patients. Despite not having active bleeds at the time of sample withdrawal, both ENG mRNA expression and ENG protein were elevated in haemophilia patients compared to control subjects, suggesting that chronic inflammatory conditions might induce a continuous state of neo-angiogenesis and joint damage.…”
mentioning
confidence: 99%
“…Therefore, it is important to evaluate the pathogenesis of hemophilic arthropathy and attempt new targeted therapies [11]. VEGF plays an essential role in the pathogenesis of hemophilic arthropathy [3]. Because of such involvement, we aimed to determine whether inhibiting VEGF with intra-articular bevacizumab would also inhibit neoangiogenesis and reduce cartilage damage and synovial changes in a rabbit model of hemophilic arthropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, type A synoviocytes, after incorporating iron, produce inflammatory cytokines (IL-1β, IL-6, TNFα), in turn inducing migration of polymorphonuclear cells and, later, of monocytes and lymphocytes. This leads to a self-maintaining cycle further increasing inflammatory response and inducing an enhanced angiogenesis (Lafeber et al, 2008;Agapidou et al, 2016). Indeed, the inflamed and hypertrophic synovium has an enhanced oxygen demand, stimulating both locally and systemically the release of growth factors like vascularderived endothelial growth factor (VEGF), thus promoting neoangiogenesis (Pulles et al, 2017).…”
Section: Iron Chemical Damage In Synovitis (Figure 1)mentioning
confidence: 99%